2020
DOI: 10.2147/oajsm.s280841
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Musculoskeletal Re-Injury Occurrence in Previously Concussed National Football League Athletes</p>

Abstract: Introduction Increased risk of musculoskeletal (MSK) injury post-concussion has been reported in collegiate athletes, yet it is unknown if professional football athletes are at the same risk of secondary injury. The objective of this study was to determine if the risk of MSK injury in National Football League (NFL) athletes increases after concussion. Methods NFL injury reports from 2013 to 2017 were collected from public websites. Concussed athletes (n=91) were equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This previous work indicated that NMT participation throughout a competitive season resulted in a lower incidence of knee/ankle injury relative to a sham protocol. 8 As athletes are susceptible to sports-related injuries after concussion, 1,3,6,23,29,50 the relative effect of NMT in athletes with recent concussion as compared with standard of care may be even greater than previous observations among youth athletes who perform NMT throughout the season. 43 Indeed, in our study we observed a protective effect of NMT intervention against sustaining a sports-related time-loss injury in the year after postconcussion RTP.…”
Section: Discussionmentioning
confidence: 99%
“…This previous work indicated that NMT participation throughout a competitive season resulted in a lower incidence of knee/ankle injury relative to a sham protocol. 8 As athletes are susceptible to sports-related injuries after concussion, 1,3,6,23,29,50 the relative effect of NMT in athletes with recent concussion as compared with standard of care may be even greater than previous observations among youth athletes who perform NMT throughout the season. 43 Indeed, in our study we observed a protective effect of NMT intervention against sustaining a sports-related time-loss injury in the year after postconcussion RTP.…”
Section: Discussionmentioning
confidence: 99%